PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MEMAHAMI VOKAL TEMBANG BALI - I Ketut Muada; I Wayan Sugama; Luh De Liska (Widyadari : Jurnal Pendidikan, 2022)
This study aims to determine students' learning abilities in Balinese tembang material, as well as student responses to the use of problem based learning learning models in Balinese vocal tembang courses in students in the fourth semester of Sendratasik 2021/2022. The existence of tembang plays a very important role in society, because tembang/metembang is often associated with aspects of ritual, entertainment/spectacle in the form of sekar rare, alit, middle and agung. This study will discuss students' abilities and student responses to the Balinese tembang vocal material by using a problem based learning model with two assessment methods, namely test and observation methods. The results showed that before the application of the problem based learning model, the average score of students was 47.7. After the application of the problem based learning model, there was an increase in the achievement of student scores in the first cycle to an average of 67.7, the average student response reaching 58.2. In cycle II, there was a significant increase, namely the achievement of the average score of students reaching 80, while student responses increased, reaching 76.2 in cycle II.